The combined measurement of high-sensitivity cardiac troponins and natriuretic peptides: a useful tool for clinicians?. Issue 12 (December 2020) - Perrone, Marco A.; Zaninotto, Martina; Masotti, Silvia; Musetti, Veronica; Padoan, Andrea; Prontera, Concetta; Plebani, Mario; Passino, Claudio; Romeo, Francesco; Bernardini, Sergio; Clerico, Aldo
Abstract : N/A: An enormous amount of experimental and clinical evidence has clearly shown that the measurement of cardio-specific biomarkers is able to significantly and independently improve the diagnostic accuracy and risk stratification in cardiovascular diseases. Furthermore, many recent studies have reported that the measurement of cardio-specific biomarkers has a positive impact also on the management and outcome of patients with cardiovascular diseases. Considering the significant and independent information associated with cardio-specific biomarkers, several studies have recently reported that the combined dosage of natriuretic peptides and cardiac troponins may be convenient not only for the diagnosis, prognosis, and treatment of heart disease, but also for general screening of the population for individuals with high cardiovascular risk. Due to the higher cost of cardio-specific biomarkers compared with other laboratory tests, the clinical adequacy of the combined measurement of natriuretic peptides and cardiac troponins must be carefully evaluated. Consequently, an increase in the clinical use of a laboratory test should be based not only on the favorable pathophysiological characteristics of a biomarker, but also on the high performance of the methods used for biomarker dosing. The purpose of this review is to discuss the clinical relevance and the possible cost efficiency of the combined dosage of natriuretic peptides and cardiac troponins in some clinical conditions, in particular those most frequently observed in patients with critical illnesses admitted to the emergency room.